"The Role of Strategic Planning in Achieving Organizational Agility for Public Institutions: An Applied Study on Some Egyptian Government Banks" - Elwkeel, Eman (The Arab Journal of Administration, 2022)
The study aimed to examine the role of strategic planning in achieving organizational agility in government banks in Egypt, and focused on this relationship in terms of planning practices using scenario analysis, planning practices using sowt analysis, short and long-term planning practices, as independent variables, organizational agility in government banks in Egypt, Dependent variable. The results came to confirm at the level of significance (α≤0.05) the presence of a correlation and impact between strategic planning and organizational agility in government banks in Egypt, as it was found that there is a correlation and effect between planning practices using scenario analysis and organizational agility in government banks in Egypt, a correlation and influence between Planning practices using sowt analysis and organizational agility, short and long planning practices and organizational agility at a significant level (α≤0.05). Among the most important things suggested by the study is the need for banks to spread the culture of strategic planning at all organizational and human levels, that banks work to implement strategic planning in accordance with the themes of planning using scenario analysis, planning using sowt analysis, short and long-term planning, enhancing organizational agility through Focusing on assuring the ease and speed of decision-making, the speed of application of technologies and technology in its banking services, the speed of adjusting its internal banking operations, in light of the developments facing the Egyptian banking sector